Treating atrial fibrillation in the 21st Century: part 1. (2nd January 2019) - Redpath, Adam; Bowen, Mark
Abstract : Atrial fibrillation (AF) is the most common pathological cardiac arrhythmia in the horse. While it may be an incidental finding in some horses, it can be an important cause of poor exercise tolerance in the performance horse, especially those working at extremes of cardiac function. Although quinidine sulfate remains the most widely used treatment option for horses, alternatives, such as transvenous electrocardioversion, are growing in popularity. The decision-making process to establish the most appropriate treatment is based on a number of factors including chronicity, underlying disease, and cardiac size. The availability of transvenous electrocardioversion in the horse provides a valid alternative for the treatment of horses with atrial fibrillation.